Preliminary evidence that vortioxetine may improve sleep quality in depressed patients with insomnia: a retrospective questionnaire analysis. Issue 1 (24th October 2018) - Liguori, C.; Ferini‐Strambi, L.; Izzi, F.; Mari, L.; Manfredi, N.; D'Elia, A.; Mercuri, N. B.; Placidi, F.
Abstract : Insomnia is a frequent symptom in depressed patients. It can present with difficulty in initiating and/or maintaining sleep. We retrospectively evaluated a group of 15 patients affected by major depressive disorder and complaining of insomnia, who started vortioxetine (VOR) treatment for their depressive symptoms. The following questionnaires were captured at baseline and follow‐up: Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and Beck Depression Inventory. Pittsburgh Sleep Quality Index total score significantly decreased between follow‐up and baseline ( P <  0.01), and in several subitems related to sleep quality and continuity. Moreover, Epworth Sleepiness Scale decreased between follow‐up and baseline ( P <  0.01). Finally, Beck Depression Inventory reduction was also evident between follow‐up and baseline ( P <  0.01). This retrospective analysis showing the significant effect of VOR on both depressive symptoms and insomnia in patients showing comorbid major depressive disorder and insomnia invites further research in order to confirm this preliminary evidence. We hypothesize that the VOR mechanism of action may explain the improvement of subjective sleep, other than depressive symptoms.